2022
DOI: 10.1038/s41598-021-04393-3
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high upper critical field in BiCh2-based (Ch: S and Se) layered superconductor LaO0.5F0.5BiS2−xSex (x = 0.22 and 0.69)

Abstract: Centrosymmetric compounds with local inversion symmetry breaking have tremendously interesting and intriguing physical properties. In this study, we focus on a BiCh2-based (Ch: S, Se) layered superconductor, as a system with local inversion asymmetry, because spin polarisation based on the Rashba–Dresselhaus-type spin–orbit coupling has been observed in centrosymmetric BiCh2-based LaOBiS2 systems, while the BiCh2 layer lacks local inversion symmetry. Herein, we report the existence of extremely high in-plane u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…However, the experimental data derived from the WHH curves in the low-temperature region are shown in figures 8(b) and (d). A similar behavior was observed for LaO 0.5 F 0.5 BiS 2-x Se x [23,50]. Although the origin of this behavior is currently unclear, the two-gap model fits well with the experimental data for LaO 0.5 F 0.5 BiS 2 [24].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…However, the experimental data derived from the WHH curves in the low-temperature region are shown in figures 8(b) and (d). A similar behavior was observed for LaO 0.5 F 0.5 BiS 2-x Se x [23,50]. Although the origin of this behavior is currently unclear, the two-gap model fits well with the experimental data for LaO 0.5 F 0.5 BiS 2 [24].…”
Section: Resultssupporting
confidence: 81%
“…However, the specific heat measurement of LaO 0.5 F 0.5 BiSSe single crystals indicates a single-gap nature [50]. We suggested that local inversion asymmetry enhances the Pauli limit in LaO 0.5 F 0.5 BiS 2-x Se x (x=0.22, 0.69) single crystals [23]. In tetragonal systems with the Rashba-type ASOC, some components of magnetic susceptibility do not change after the superconducting transition, resulting in protection of the Cooper pairs from de-pairing against the applied fields [18, 24, 53].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…With increasing magnetic field, the layers become increasingly decoupled, such that δ → 0 and the spatial modulation decreases, similar to the J = 0 case. This picture is consistent with similar results seen within a BdG approach (91,92) and could be realized in LaO0.5F0.5BiS2−xSex (x = 0.22, 0.69) (34). Finally, note that incorporation of orbital effects in a multi-layer system may stabilize an odd-parity superconducting state similar to that discussed in Sec.…”
Section: From Helical Phase To Complex Stripe Phasesupporting
confidence: 90%
“…A symmorphic example, illustrated in Figure 2a, is the quasi-tetragonal cuprate Bi2Sr2CaCu2O 8+δ (Bi2212) (29,30,31,32). This class further includes the tetragonal CeRh2As2 (33) and the family of BiS2−nSen superconductors, such as LaO0.5Fe0.5BiSe2 (34), all showing intriguing magnetic properties. They crystalize in the nonsymmorphic P4/nmm space group (#129) with generating point group D 4h , see Figure 2b for examples.…”
Section: Examples Of Locally Noncentrosymmetric Superconductorsmentioning
confidence: 99%